2011
DOI: 10.1093/brain/awq376
|View full text |Cite
|
Sign up to set email alerts
|

Troxerutin protects against high cholesterol-induced cognitive deficits in mice

Abstract: Recent findings suggest that neurotoxicity is the mechanism underlying the induction of neuronal insulin resistance by a high cholesterol diet. Troxerutin, a naturally occurring flavonoid, has been reported to possess biological activity beneficial to human health. Our recent studies have demonstrated that troxerutin attenuates cognitive impairment and oxidative stress induced by D-galactose in mouse brain through decreasing advanced glycation end products, reactive oxygen species and protein carbonyl levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 40 publications
4
80
1
1
Order By: Relevance
“…Supplementation of TX enhanced IRβ and IRS-1 tyrosine phsphorylation, IRS-1-PI3K association thereby improves Akt activation in HFFDfed mice. Our findings are similar to that of Lu et al 26 reported that TX administration significantly improved insulin sensitivity in high-cholesterol-fed mice by increasing the serine phosphorylation of Akt which is due to activation of tyrosine phosphorylation of IR and IRS-1. Insulin induces the translocation of GLUT-4 from the intracellular storage to the sarcolemmal membrane and so favours glucose entry.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Supplementation of TX enhanced IRβ and IRS-1 tyrosine phsphorylation, IRS-1-PI3K association thereby improves Akt activation in HFFDfed mice. Our findings are similar to that of Lu et al 26 reported that TX administration significantly improved insulin sensitivity in high-cholesterol-fed mice by increasing the serine phosphorylation of Akt which is due to activation of tyrosine phosphorylation of IR and IRS-1. Insulin induces the translocation of GLUT-4 from the intracellular storage to the sarcolemmal membrane and so favours glucose entry.…”
Section: Discussionsupporting
confidence: 92%
“…A study reported that that TX administration strongly inhibits the activation of JNK1 and IKKβ/NF-κB induced by endoplasmic reticulum stress in the hippocampus of highcholesterol-fed mice. 26 Further, our previous study also demonstrated the lipid-lowering effects of TX. 6 Akt/protein kinase B, a serine/threonine kinase is the downstream target of insulin signaling cascade that activates glucose uptake through GLUT-4.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A guillotine door separated the two compartments. The step-through test was conducted as previously described (31). In brief, the mice were placed in a dimly lit room, which contained the apparatus, for 0.5 h before training to allow the mice to acclimatize to their new environment.…”
Section: Morris Water Maze Testmentioning
confidence: 99%
“…Our previous studies have demonstrated that troxerutin has many different biological activities, including antioxidant and anti-inflammatory activities (27)(28)(29)(30)(31). Recently, our preliminary data showed that troxerutin blocked the phosphorylation of MAPK/ ERK1/2 (MEK1/2) in the hippocampus of DA-treated mice and reversed DA-induced memory deficits.…”
mentioning
confidence: 95%